Cell Migration Is Regulated by AGE-RAGE Interaction in Human Oral Cancer Cells In Vitro - Ko, Shun-Yao; Ko, Hshin-An; Shieh, Tzong-Ming; Chang, Weng-Cheng; Chen, Hong-I; Chang, Shu-Shing; Lin, I-Hsuan (PloS one, 2014)
Advanced glycation end products (AGEs) are produced in an irreversible non-enzymatic reaction of carbohydrates and proteins. Patients with diabetes mellitus (DM) are known to have elevated AGE levels, which is viewed as a risk factor of diabetes-related complications. In a clinical setting, it has been shown that patients with oral cancer in conjunction with DM have a higher likelihood of cancer metastasis and lower cancer survival rates. AGE-RAGE (a receptor of AGEs) is also correlated with metastasis and angiogenesis. Recent studies have suggested that the malignancy of cancer may be enhanced by glyceraldehyde-derived AGEs; however, the underlying mechanism remains unclear. This study examined the apparently close correlation between AGE-RAGE and the malignancy of SAS oral cancer cell line. In this study, AGEs increased ERK phosphorylation, enhanced cell migration, and promoted the expression of RAGE, MMP2, and MMP9. Using PD98059, RAGE antibody, and RAGE RNAi to block RAGE pathway resulted in the inhibition of ERK phosphorylation. Cell migration, MMP2 and MMP9 expression were also reduced by this treatment. Our findings demonstrate the importance of AGE-RAGE with regard to the malignancy of oral cancer, and help to explain the poor prognosis of DM subjects with oral cancer.